Effect of signal processing strategy and stimulation type on speech and auditory perception in adult cochlear implant users. - Reynolds, Susan M.; Gifford, René H. (International Journal of Audiology, 2019)
Objective: The objective of this study was to investigate the effects of signal processing strategy on speech understanding and auditory function for adult cochlear implant (CI) users with a focus on the effects of sequential versus paired stimulation. Design: Within-subjects, repeated measures design was utilised to compare performance between processing strategies and stimulation type on various measures of auditory function and subjective sound quality. Testing with subsequent strategies was completed after a total familiarisation time of two weeks. Study Sample: Ten post-lingually deafened adult CI users were recruited from a clinical population. Participants had a minimum of 13 months CI experience. Ages ranged from 25–78 years. All participants had long-term experience with the optima strategy; eight with sequential stimulation and two with paired stimulation. Results: We found no statistically significant effect of processing strategy. We observed an effect of stimulation type with sequential stimulation yielding significantly higher performance than paired stimulation for speech understanding in quiet and in noise, and subjective estimates of sound quality. No significant differences were noted across strategy or stimulation for music perception, spectral resolution or temporal resolution. Conclusions: Many patients utilise paired stimulation – the default stimulation type in the clinical software; however, sequential stimulation yielded significantly higher outcomes on multiple measures.